2022
DOI: 10.1038/s41598-022-12306-1
|View full text |Cite
|
Sign up to set email alerts
|

The 2D:4D index is associated with the development of excess body weight in adults, but not with the rate of weight loss following bariatric surgery

Abstract: Abstract2D:4D finger length ratio is a proxy of prenatal sex hormone exposure. Prenatal testosterone decreases and prenatal estrogens increase this index. In the current study we investigated whether the 2D:4D index, as a marker of the prenatal hormonal environment, is associated with the development of overweight and obesity in adults, and whether is it correlated with the rate of weight loss in patients after bariatric surgery. We tested 125 adults with obesity (BMI ≥ 30.0 kg/m2), 125 adults with overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Different studies have also shown an association (or lack of association) of several digit measures and ratios with child and adolescent obesity [49] or child body composition [50]. In adult populations, different studies showed that excessive body weight in men and women, and fat accumulation in the upper arms, thighs, and lower legs in women with obesity, are associated with increased prenatal estrogen exposure as measured through 2D:4D [51]. As some authors suggested, this relationship could be of relevance in the field of obesity prevention, as the 2D:4D index (especially of the right hand) may be a useful marker in the early prediction of the elevated risk of developing excessive body weight in humans, although other relevant factors such as eating habits and lifestyle must be taken into account [51].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have also shown an association (or lack of association) of several digit measures and ratios with child and adolescent obesity [49] or child body composition [50]. In adult populations, different studies showed that excessive body weight in men and women, and fat accumulation in the upper arms, thighs, and lower legs in women with obesity, are associated with increased prenatal estrogen exposure as measured through 2D:4D [51]. As some authors suggested, this relationship could be of relevance in the field of obesity prevention, as the 2D:4D index (especially of the right hand) may be a useful marker in the early prediction of the elevated risk of developing excessive body weight in humans, although other relevant factors such as eating habits and lifestyle must be taken into account [51].…”
Section: Discussionmentioning
confidence: 99%
“…The data collected on problem solving related to quality was tested using the oneshot case method, which later resulted in a quality and effective model. This development research was to improve the existing management model with a new management model which later be assessed for its implementation and effectiveness (Iljin et al, 2022;Lukin et al, 2019).…”
Section: Disseminatementioning
confidence: 99%